2019
DOI: 10.1534/g3.119.400762
|View full text |Cite
|
Sign up to set email alerts
|

Genome Assemblies of Two Rare Opportunistic Yeast Pathogens:Diutina rugosa(syn.Candida rugosa) andTrichomonascus ciferrii(syn.Candida ciferrii)

Abstract: Infections caused by opportunistic yeast pathogens have increased over the last years. These infections can be originated by a large number of diverse yeast species of varying incidence, and with distinct clinically relevant phenotypic traits, such as different susceptibility profiles to antifungal drugs, which challenge diagnosis and treatment. Diutina rugosa (syn. Candida rugosa) and Trichomonascus ciferrii (syn. Candida ciferrii) are two opportunistic rare yeast pathogens, which low incidence (< 1%) limits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Our results revealed that C. subhashii has 501 orphan genes, and that genes specifically duplicated in this species are enriched in transmembrane transport activity ( Supplementary File S2 ). This result is similar to what was previously obtained for other Candida pathogens, such as C. inconspicua , Diutina (Candida) rugosa and Trichomonascus (Candida) ciferrii , 7 , 28 and reinforces the previously proposed hypothesis that cell wall composition may play a role in the adoption of an opportunistic pathogenic behaviour by Candida species. 38 As previous reports suggest that the human body is not the main habitat of C. subhashii , 12 we hypothesize that the duplication of cell wall proteins must have been advantageous in non-human environments while perhaps secondarily facilitating opportunistic colonization of humans.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our results revealed that C. subhashii has 501 orphan genes, and that genes specifically duplicated in this species are enriched in transmembrane transport activity ( Supplementary File S2 ). This result is similar to what was previously obtained for other Candida pathogens, such as C. inconspicua , Diutina (Candida) rugosa and Trichomonascus (Candida) ciferrii , 7 , 28 and reinforces the previously proposed hypothesis that cell wall composition may play a role in the adoption of an opportunistic pathogenic behaviour by Candida species. 38 As previous reports suggest that the human body is not the main habitat of C. subhashii , 12 we hypothesize that the duplication of cell wall proteins must have been advantageous in non-human environments while perhaps secondarily facilitating opportunistic colonization of humans.…”
Section: Resultssupporting
confidence: 91%
“…Mitochondria-related genes were identified with TargetP v1. 27 Phylome reconstruction was performed as previously described 28 and deposited in the PhylomeDB database ( http://beta.phylomedb.org, 31 May 2021, date last accessed ). 29 Phylome results were used to infer orthology and paralogy relations and determine the associated GO terms.…”
Section: Methodsmentioning
confidence: 99%
“…Stephanoascus ciferrii , which is first discovered in 1965, is an opportunistic rare yeast pathogen with low prevalence (<1% of clinical Candida infections) ( Kreger-Van Rij, 1965 ; Mixao et al, 2019 ). The literature about S. ciferrii is limited, and it is usually reported in some sporadic cases of infections ( Villanueva-Lozano et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…PhylomeDB pipeline 43 was used for phylome reconstruction as described in Mixão et al, 44 considering the 28 species specified in Supplementary File S1 , and using each of the five target species of this study as seed. Gene gain and loss analysis in the seed branch was performed based on the phylome results.…”
Section: Methodsmentioning
confidence: 99%